2012
DOI: 10.1615/critrevimmunol.v32.i4.10
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Roles of the Tumor Necrosis Factor Receptor BCMA

Abstract: B cell maturation antigen (BCMA) is a tumor necrosis family receptor (TNFR) member that is predominantly expressed on terminally differentiated B cells and, upon binding to its ligands B cell activator of the TNF family (BAFF) and a proliferation inducing ligand (APRIL), delivers pro-survival cell signals. Thus, BCMA is most known for its functional activity in mediating the survival of plasma cells that maintain long-term humoral immunity. The expression of BCMA has been also linked to a number of cancers, au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(68 citation statements)
references
References 91 publications
0
68
0
Order By: Relevance
“…21,[35][36][37] Based on this, we also anticipated observing increased numbers of these effector B-cell populations in hBAFFKI hu-mice, a hypothesis supported by studies in which injection of hBAFF in hu-PBL and hu-mice improved thymusindependent antibody responses to the Pneumovax vaccine. 19,20 Our linear regression analyses comparing naive B cells and memory B cells or plasmablasts in hu-mice indicated a correlation between effector and naive cell populations.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…21,[35][36][37] Based on this, we also anticipated observing increased numbers of these effector B-cell populations in hBAFFKI hu-mice, a hypothesis supported by studies in which injection of hBAFF in hu-PBL and hu-mice improved thymusindependent antibody responses to the Pneumovax vaccine. 19,20 Our linear regression analyses comparing naive B cells and memory B cells or plasmablasts in hu-mice indicated a correlation between effector and naive cell populations.…”
Section: Discussionmentioning
confidence: 73%
“…21,[35][36][37] To determine whether expression of hBAFF impacted the distribution of these effector B cells in hu-mice, we used flow cytometry to quantify cells with this phenotype (Figure 5A-C …”
Section: Development Of Terminally Differentiated B Cells and Antibodiesmentioning
confidence: 99%
“…Thus, it seems that both APRIL and BAFF can act as agonists in vivo for membrane-bound BCMA. Coquery and Erickson [43] detected no BCMA on the surface of normal mature murine B cells, and the levels on the surface of plasma cells were modest. RNase protection assays showed that BCMA mRNA is expressed predominantly in terminally differentiating and immunoglobulin secreting B cell lines [43].…”
Section: Bcmamentioning
confidence: 96%
“…APRIL and BAFF bind to TACI with equal affinity, and APRIL binds BCMA with higher affinity than BAFF [28][29][30][31][32][33][34][35]. Bone marrow PCs from Bcm-knockout mice have a lower survival rate compared with those from wild-type mice, indicating that signal transduction through BCMA is related to the long-term survival of PCs [3,11,36]. The pattern of temporal expression of BAFF suggests that it acts during earlier stages of B-cell differentiation than APRIL.…”
Section: Discussionmentioning
confidence: 99%
“…APRIL signaling through its receptors, which are the members of the TNF receptor family, B-cell maturation antigen (BCMA), and transmembrane activator and calcium modulator and cyclophilin ligand interactor (TACI), mediates the late stage of B cell development [5][6][7][8][9][10][11]. In a mouse model, APRIL deficiency decreases the ability of the bone marrow to support plasma cell (PC) survival [12].…”
Section: Introductionmentioning
confidence: 99%